Help-seeking strategy for developing reading skills of Iraqi EFL students - Mohammed Alnoori, Bushra Sadoon (Opción, 2019)
The aim of the study is to investigate the help-seeking strategy for developing reading skills and observing the attitude of Iraqi EFL students via statistical analysis research method. T-score was calculated to understand the difference between the performance in pre-test and post-test. As a result, help-seeking is a useful strategy that accelerates the process of learning without having to obstruct the flow of reading. In conclusion, the results of the study show beyond doubt that in maximum cases, help-seeking proves to be successful for EFL students at the first-year college level.